Epistemologi Amal dalam Tiga Aliran Teologi Islam: Analisis Komparatif Khowarij, Murji’ah, dan Ahlussunnah - Tofan Rinaldi; Benni Prasetya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The debate concerning the relationship between faith (īmān) and deeds (ʿamal) constitutes one of the central issues in the history of Islamic theology, generating diverse perspectives among theological schools. This study aims to comparatively analyze the epistemology of deeds in three classical Islamic theological traditions: Khawarij, Murji’ah, and Ahlussunnah. The research employs a qualitative approach using the integrative literature review method, examining classical works of ʿilm al-kalām alongside contemporary academic studies. The data were analyzed through data reduction, thematic categorization, and comparative analysis to identify differences in the epistemological frameworks used to understand the relationship between faith and deeds. The findings indicate that the Khawarij developed a textual–legalistic epistemology that considers deeds an essential component of faith, thereby viewing perpetrators of major sins as having exited the state of faith. In contrast, the Murji’ah developed a theological–rational epistemology that separates faith from deeds and postpones judgment regarding major sinners to God’s ultimate decision. Meanwhile, Ahlussunnah formulated an integrative epistemology that combines belief in the heart, verbal affirmation, and deeds within the structure of faith without declaring major sinners as unbelievers. This study highlights that differences in the concept of deeds in Islamic theology are not merely doctrinal but also reflect distinct epistemological frameworks in interpreting religious sources. The findings contribute conceptually to the study of ʿilm al-kalām by offering a comparative mapping of the epistemology of deeds across three major theological traditions in Islam.